2019
DOI: 10.1208/s12249-019-1377-0
|View full text |Cite
|
Sign up to set email alerts
|

Preformulation and Evaluation of Tofacitinib as a Therapeutic Treatment for Asthma

Abstract: Preformulation studies on tofacitinib citrate, a small molecule JAK3 specific inhibitor, have not been previously reported in literature. We therefore conducted several preformulation studies on tofacitinib citrate, and its free base, to better understand factors that affect its solubility, stability, and solid-state characteristics. Further, the results of the preformulation studies helped facilitate the development of a nebulized formulation of tofacitinib citrate for inhalational delivery to house dust mite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…In general, the pristine drugs showed crystalline or semi-crystalline structure, and they underwent substantial amorphization upon nanonization, as clear from the broadening and, in some cases, the disappearance, of the diffraction peaks that are characteristic of the crystalline drug ( Figure 5 ). For example, in the diffractogram of TOF, the raw drug showed a considerably high crystallinity as demonstrated by a series of sharp and intense diffraction peaks ( Figure 5 c) in accordance with literature [ 93 ]. Conversely, nanonized TOF formed a halo pattern typical of a substantially amorphous material, except for two peaks at 2θ = 31.7 and 2θ = 45.5 that were not observed in the XRD pattern of raw TOF ( Figure 5 c).…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In general, the pristine drugs showed crystalline or semi-crystalline structure, and they underwent substantial amorphization upon nanonization, as clear from the broadening and, in some cases, the disappearance, of the diffraction peaks that are characteristic of the crystalline drug ( Figure 5 ). For example, in the diffractogram of TOF, the raw drug showed a considerably high crystallinity as demonstrated by a series of sharp and intense diffraction peaks ( Figure 5 c) in accordance with literature [ 93 ]. Conversely, nanonized TOF formed a halo pattern typical of a substantially amorphous material, except for two peaks at 2θ = 31.7 and 2θ = 45.5 that were not observed in the XRD pattern of raw TOF ( Figure 5 c).…”
Section: Resultssupporting
confidence: 86%
“…Pristine IMA showed melting temperature ( T m ) at 215 °C ( Figure 6 ). Pristine DAS and TOF showed two melting temperatures at 287 and 318 °C and at 148 and 168 °C, respectively, suggesting the presence of a mixture of different polymorphs [ 93 , 94 , 97 ]. The transitions in pristine TOF were very weak with very broad peaks ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This indicates that nearly 75% of tofacitinib was degraded. The observed base degradation result was confirmed with the reported study by Younis et al They reported that above the pH ~ 9, tofacitinib citrate showed the highest degree of degradation [37]. In contrast, under oxidative stress conditions, the chromatogram (Fig.…”
Section: Specificitysupporting
confidence: 90%
“…To solve the problem, a series of anti-inflammatory mediators with different pathogenic targets have been proposed to asthma treatment (Celotti and Laufer, 2001;Zhu et al, 2018). Besides well-known omalizumab (Strunk and Bloomberg, 2006), mepolizumab (Ortega et al, 2014) and benralizumab (Nair et al, 2017), tofacitinib, a Janus kinase-signal transducers and activators of transcription (JAK-STAT) signal inhibitor, has exhibited anti-inflammatory effects in murine asthma models and represent the potential to be an effective treatment for asthma (Younis et al, 2019). Accumulating evidence indicated that anti-inflammatory drugs could exert strong efficacy in asthma patients, which enlighten us that developing new uses of already-approved agents with anti-inflammatory properties might be a simple and effective way to pursue innovation of asthma drugs.…”
Section: Introductionmentioning
confidence: 99%